Green Healthcare Accountability: A Comprehensive Review of Environmental Accounting in Hospitals - Batara, I Wayan Darma; Permata, Marchelo Boas; Putri, Sofie Yunida; Wilasittha, Acynthia Ayu; Widajantie, Tituk Diah (Nusantara Science and Technology Proceedings, 2023)
This literature review aims to provide insights into the utilization of environmental accounting within the healthcare sector. The primary objective is to comprehensively analyze the prior study to understand the rationale, methodologies, and results associated with implementing environmental accounting practices within hospital settings. The research methodology employed in this evaluation encompassed a comprehensive analysis of the relevant scholarly literature. The literature review findings indicate that hospitals utilize environmental accounting methods for a range of purposes, such as ensuring adherence to regulatory requirements, achieving financial savings, enhancing their reputation, and fulfilling their social responsibilities. This paper also investigates the methodologies and tools commonly utilized in hospital settings for environmental accounting. These include carbon accounting, waste management accounting, energy consumption monitoring, and eco-efficiency analysis. This study investigates the impact of environmental accounting on hospitals' financial reports and decision-making processes. The use of environmental accounting practices can have a significant effect on the resource allocation, investment decisions, and long-term strategic planning of healthcare organizations. This literature analysis highlights the imperative for further research in this domain and underscores the increasing importance of environmental accounting within healthcare institutions. The findings underscore the significance of incorporating sustainability into the management practices of hospitals, indicating that implementing environmental accounting methods can substantially influence the financial and environmental performance of healthcare organizations